PENGARUH FASILITAS, HARGA, DAN LABEL HALAL TERHADAP KEPUTUSAN MENGINAP DI SOFYAN HOTEL CUT MEUTIA - Muhammad Akmal Ramadhan, (2023)
Indonesia is one of the top ten countries for halal tourism destinations. Halal tourism certainly needs lodging such as hotels. Sharia hotels are one of the things that attract the attention of the Muslim community to stay. In this study, the aim was to find out whether facilities, prices, and halal labels affect the decision to stay at Sofyan Hotel Cut Meutia by hotel consumers. The research method used is quantitative data, with primary data collection through distributing questionnaires using purposive sampling method. Data analysis techniques in this study were tested using PLS. The value of the r-square is 0.469, it is concluded that facilities, price, and halal labels can explain the variable of the decision to stay by 46.9% and 53.1% is explained through other variables outside this study. The results of the hypothesis test are that facilities have no significant effect on the decision to stay, then price has a significant effect on the decision to stay, and the halal label has a significant effect on the decision to stay. Researchers hope to provide benefits for further research and sharia hotel companies.